Fraud Pentagon for Detecting Financial Statement Fraud - Ananda Putra Nindhita Aulia Haqq; Gideon Setyo Budiwitjaksono (Universitas Hayam Wuruk Perbanas, 2019)
A financial statement is a result of financial reporting that describes the results of an entity’s financial performance for a specified period. Financial statements can also cause managers in an entity to commit financial reporting fraud because they want to describe an excellent financial performance. This study aims to test fraud pentagon theory in detecting fraudulent financial reporting. More specifically, this study attempts to test the financial target, financial stability, external pressure, ineffective monitoring, nature of the industry, change in auditor, change in director, CEOs photo frequency, political connection, and company existence against fraudulence in the companies' financial reporting. These companies are classified in the LQ45 index on the Indonesian Stock Exchange (IDX) during the period 2015-2017. It used 78 annual report data taken by a proportional random sampling based on the number of proportions in each sector of the company. The data were analyzed using multiple regression analysis. The results indicate that financial stability and CEO photo frequency can be used to detect fraudulence in financial reporting. However, financial targets, external pressure, ineffective monitoring, nature of the industry, changes in auditor, changes in director, political connection, and company existence cannot be used to detect fraudulence in financial reporting.